Series of Near-IR-Absorbing Transition Metal Complexes with Redox Active Ligands - Esko Salojärvi; Anssi Peuronen; Manu Lahtinen; Hannu Huhtinen; Leonid S. Vlasenko; Mika Lastusaari; Ari Lehtonen (Molecules, 2020)
New soluble and intensely near-IR-absorbing transition metal (Ti, Zr, V, Ni) complexes were synthesized using a redox non-innocent N,N’-bis(3,5-di-tertbutyl-2-hydroxy-phenyl) -1,2-phenylenediamine (H4L) as a ligand precursor. In all the complexes, ([Ti(Lox)2, [Zr(Lox)2], [V(Lsq1)(HLox)] and [Ni(HLox)2], two organic molecules coordinate to the metal center as tri- or tetradentate ligands. The solid-state structures of the complexes were determined using single crystal XRD, and the compounds were further characterized with Electrospray Ionisation Mass Spectrometry (ESI-MS). Thermoanalytical measurements indicated the thermal stabilities of the complexes. All compounds absorb strongly in the near-IR region and show very interesting magnetic and electrochemical properties. Moreover, it was shown that the V and Ni complexes can also convert absorbed near-IR photons to (un)paired electrons, which indicates great promise in photovoltaic applications.